Proceedings of the International Conference on Science and Education and Technology 2018 (ISET 2018) 2018
DOI: 10.2991/iset-18.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Simple Harmonic Vibration Student Learning Worksheet (LKPD) based on Curious Note Program (CNP) Learning Model in Improving Students’ Creative Thinking Ability

Abstract: This research aims to analyze the feasibility, praticality, and effectiveness of Simple Harmonic Vibration student learning worksheet (LKPD) based on Curious Note Program (CNP) learning model which can improve the students' creative thinking ability. The research was categorized as Reasearch and Development (R&D) study which refers to a model 4-D. The data were collected by using sheet questionnaire of syllabus validation, lesson plan (RPP) validation, student learning worksheet (LKPD) validation, questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…(2018) that is Simple Harmonic Vibration student learning worksheet based on Curious Note Program (CNP) learning model obtained the value 91%, 90%, and 91% as a valid category. It can be concluded that this worksheet is feasible and practical to be used for learning and effective activities to improve the creative thinking ability of learners [13].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…(2018) that is Simple Harmonic Vibration student learning worksheet based on Curious Note Program (CNP) learning model obtained the value 91%, 90%, and 91% as a valid category. It can be concluded that this worksheet is feasible and practical to be used for learning and effective activities to improve the creative thinking ability of learners [13].…”
Section: Resultsmentioning
confidence: 96%
“…Based on research conducted by Farumananda, et, al. (2018) that is Simple Harmonic Vibration student learning worksheet based on Curious Note Program (CNP) learning model obtained the value 91%, 90%, and 91% as a valid category.…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini mengimplikasikan bahwa peserta didik tingkat sekolah menengah khususnya yang menjadi responden uji coba lembar kerja CNPs menunjukkan jumlah siswa dengan kemampuan merancang eksperimen pada tingkat "baik" masih lebih sedikit dibandingkan dengan siswa yang tergolong "cukup baik". Hasil ini dapat menggambarkan bahwa peserta didik sebenarnya belum begitu mampu dalam menguasai aspek-aspek kemampuan merancang eksperimen yang diujikan dalam lembar kerja CNPs (Farumananda et al, 2018). Hal ini juga bersesuaian dengan yang dinyatakan Park, dkk (2009) yang menyebutkan bahwa fase merancang eksperimen merupakan tahap tersulit yang akan dialami peserta didik dalam proses inkuiri ilmiah.…”
Section: Gambar 2 Penguasaan Kemampuan Peserta Didik Dalam Merancangunclassified
“…Salah satu pendekatan yang sejalan dengan pembelajaran inkuiri adalah model pembelajaran Curious Note Programs (CNPs) yang dikembangkan Park, et al (2009Park, et al ( , p.1512. Model pembelajaran CNPs telah diujicobakan di salah satu sekolah negeri di Korea (Farumananda et al, 2018) dan telah dibuktikan bahwa lembar kerja CNPs mampu mendorong siswa dalam akitivitas kegiatan inkuiri secara aktif. Selama proses pembelajaran, peserta didik terlibat dalam aktivitas inkuiri untuk merangsang kemampuan saintifik seperti menemukan masalah, merancang eksperimen, merumuskan hipotesis, menyusun dasar teori, dan melaksanakan eksperimen.…”
unclassified